The Qualifications Needed by Logistics Employees in the Future Industry and its Implications in Higher Education Institutions - Sari, Latifa Ika; Prasetiawan, Andi (RSF Conference Series: Engineering and Technology, 2023)
Human resources play a fundamental role in affecting logistics companies’ performance. The advancement of technology has caused significant implications in the logistics industry. This research aims to explore the qualifications needed by logistics employees in the future industry and discuss the implications in higher education institutions. The authors used a semi-systematic review to examine five relevant research articles published in reputable journals, ranging from 2017-2022. Content Analysis was conducted to identify, analyze, and report patterns. The findings of the study revealed that there are several qualifications needed by logistics employees to perform challenging tasks in the future. Body fitness, problem-solving and decision-making, creativity and innovation, adaptability, communication, leadership, and teamwork are some of the industry's top qualifications. Higher education institutions need to anticipate the current issue of human resources. Some strategies that can be employed include integrating ICT in the teaching and learning activities to familiarize students with the use of ICT, conducting an internship program in the logistics industry to provide students with real working experience, and involving stakeholders in the curriculum review and design.